Gross regional product: study of influencers - Elena Karpenko (Hryhorii Skovoroda University in Pereiaslav, 2021)
The relevance of the research topic is determined by special attention to issues of regional development in the state policy of the Republic of Belarus, the quality of life of 78.6% of the country's population depends on the level of development of the regions under study. The problem of regional development is the growing imbalances in development between the regions of the country and, as a result, undesirable interregional migration flows of the population and a reduction in the demographic potential of a number of territories, as well as the emergence of signs of depression in a number of areas. The analysis of recent publications makes it possible to verify an ongoing interest in the issue, but the drawback of most studies is the disclosure of the issue within one particular region, or the study of the growth of GRP due to conventional factors. According to the authors, until the end of the unexplored, the dependence of the gross regional product on indirect, implicit factors remains. Particular attention is drawn to the author's indicators and their place in the GRP growth model. The aim of the study is to establish the influence of unconditional and indirect factors on the magnitude and dynamics of gross regional product, which will provide an opportunity to formalize the dependence of GRP on these factors and subsequently apply the built model in practice. The study methods used in the work are comparison, grouping, correlation-regression analysis, econometric modeling, and a systemic approach. Results of work. The present study considers a set of indicators for six regions of the Republic of Belarus for the period from 2013 to 2019. Using econometric methods of analysis, the authors built a regression model of the dependence of GRP per capita on four exogenous variables, analyzed the degree of influence of these variables and the possibility of impact on them by the state. The area of application of the study results is state policy aimed at the sustainable growth of the economies of the regions. Conclusions. In the constructed model of four exogenous variables, the unemployment rate and the rate of life of the population are most significant. However, according to the authors, in order to achieve the desired level of gross regional product, it is necessary to have a comprehensive impact on all variable models, among which, in descending order of importance, the level of unemployment, the rate of life of the population, the amount of industrial production per person employed in the economy, investment in fixed assets.